Un mal nommé machisme : Masculinités et colonialité dans la représentation nahua de la violence intrafamiliale (Alto Balsas, Mexique) - Raby, Dominique (Anthropologica, 2018)
Abstract: Domestic violence is an issue of prime importance for organized Indigenous women in Mexico. Notwithstanding, there are virtually no studies that propose a definition of domestic violence based in local representations. This article shows how women in a Nahua community of the Alto Balsas region (State of Guerrero, Mexico) explain domestic violence in terms of masculinities. Inspired by R. W. Connell’s model of masculinities and by structural anthropology, the analysis suggests that a double masculinity, one associated with “Good Living” and the other a “nahuatized” machismo, must be understood at the intersection of gender and ethnical hierarchies, in their complex relations with coloniality. These opposed representations, that show a “differential value” (Héritier), have contrasted implications in terms of domestic violence. Taking into account the distinction that Nahuas establish between these two masculinities would allow for designing programs against gendered violence from a decolonial perspective.